Vocalizations of Microhyla achatina Tschudi, 1838 (Anura: Microhylidae) from the foot hills of Mount Salak, West Java - Kurniati, Hellen (Perhimpunan Biologi Indonesia, 2013)
Vocalizations of Microhyla achatina have never been described before. The advertisement calls of six individual malesof M. achatina which originated from the foot hills of Mount Salak, West Java were recorded in September 2011 atair temperatures of 21.0ÃÂ°C-23.4ÃÂ°C. Call components were obtained from 95 calls, consisting of 855 pulses, whichwere then analyzed to obtain the characteristics of sound waves by using software of Adobe Audition 3.0 andSAP2011. Sound waves of M. achatina mainly consists of impulses whose sound spectrum ranges from 1327.5-2789.1 Hz, while the band width of the spectrum is 1461.6 Hz. Results of the analysis showed that the frequency ofthe three pulse-forming elements (dominant frequency, maximum frequency and minimum frequency) was markedlymodulated; frequency modulation was clearly visible in the minimum frequency, which was modulared by 1500 to2700 Hz modulation. The modulation of the dominant frequency and the maximum frequency was not too broad,i.e. between 3000-3500 Hz. Results of linear regression analysis of the dominant frequency versus minimum frequencyand dominant frequency versus maximum frequency showed a strong correlation between the dominant frequencyversus minimum frequency, but a weak correlation between the dominant frequency versus the maximumfrequency.Keywords: vocalization, Microhyla achatina, West Java.